The talking ape : how language evolved - Burling, Robbins (Studies in the evolution of language, 2005)
In this fascinating, mind-opening book, Robbins Burling presents the most convincing account of the origins of language ever published. He sheds new light on how language affects the way we think, behave, and relate to each other; and he gives us a deeper understanding of the nature of language itself. The author traces language back to its earliest origins among our distant ape-like forbears several million years ago and charts its growth to the time of our recent human ancestors. He offers a new account of the route by which we acquired our defining characteristic and explores the nature of language as it developed throughout the course of our evolution. He explains what the earliest forms of communication are likely to have been, how they worked, and why they were deployed. He examines the qualities of mind and brain needed to support the operations of language and the selective advantages they offered those able to use them. Robbins Burling investigates the first links between signs, sounds, and meanings and explores the beginnings and prehistories of vocabulary and grammar.; He connects work in fields extending from linguistics, sign languages, and psychology to human paleontology, evolutionary biology, and archeology. And he does all this in a crystal-clear style, constantly enlivened by flashes of wit and humor.